Analisis Tingkat Kognitif Buku Teks Matematika Kelas VII SMP - Rizkita, Dea; Suparman; Haryani, Desti (JURNAL PENDIDIKAN, 2023)
This study aims to determine the suitability of the distribution of cognitive level questions in the “Matematika Kelas VII SMP” textbook published by the Kemendikbud written by Susanto, et al (2022) and the “Matematika Kelas VII SMP” textbook written by Mairing (2020). This research is an evaluative study, using the discrepancy evaluation model. The data sources in this study were questions in the “Matematika Kelas VII SMP” textbook (Susanto, et al, 2022) (called textbook A) and the “Matematika Kelas VII SMP”  textbook (Mairing, 2020) (called textbook B). Samples were taken using a proportional stratification random sampling technique to determine the number of samples taken in each chapter and the questions that became the research sample. The analysis of textbook questions was based on the cognitive level of the Revised Bloom's Taxonomy, and was evaluated by comparing the distribution of textbook cognitive levels to the cognitive dimensions of the TIMSS 2015 Assessment Framework. Of the 135 questions analyzed in textbook A, the distribution of cognitive levels was 14.8% remembering, 46.7% understanding, 20.7% applying, 9.6% analyzing, 4.5% evaluating, 3.7% creating. Meanwhile, of the 188 questions analyzed in textbook B, the distribution of cognitive levels was 0.5% remembering, 40% understanding, 40.4% applying, 11.2% analyzing, 7.4% evaluating, and 0.5% creating. The results showed that the questions in textbooks A and B were quite good because there were each cognitive level according to the Revised Bloom's Taxonomy in both textbooks. However, the distribution of cognitive levels in textbooks A and B still does not match the proportions of the TIMSS 2015 cognitive dimensions. The distribution of cognitive levels according to the TIMSS 2015 Assessment Framework is 35% knowing (remembering and understanding), 45% applying (applying), and 25% reasoning (analyze, evaluate, and create). Realization of the findings in textbook A is 61.5% knowing, 20.7% applying, and 17.8% reasoning. While the distribution in textbook B is 40.5% knowing, 40.4% applying, and 19.1% reasoning. Both textbooks are still lacking in questions of the reasoning type (analyze, evaluate, create). Thus, both textbooks are of fairly good quality, but improvements need to be made by adding questions at the cognitive level of analyzing, evaluating, and creating.